Práxis da alfabetização freiriana mediada pela comunicação suplementar alternativa: apresentação de um procedimento didático - Camalionte, Daniele de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Based on the assumptions of the cultural- historical theory, the Paulo Freire literacy method and the Assistive Technology resources, using the Prancha Fácil software as a didactic resource, this research was developed within the thematic of educating for students with disability. The main objective was to develop Freire literacy strategies for a child with Worster-Drought syndrome hypothesis, using as an auxiliary tool the Alternative Supplementary Communication. The collaborative and interventionist research, a case study, which its methodology resulted in a large corpus of dialogue between the subject of this research, his teacher and the researcher, generated during the process of pedagogic intervention for the literacy of a disabled child, inside the context of a specific resource room. The data was treated with a qualitative interpretation approach and from that were obtained some inferences. From the thought function, the results of generalization tests indicates that the subject has a cognitive performance similar to children in the same age. About the writing function, the results indicate the M.A. takes the speaking of somebody else for makes his one, since he needs assistance and mediation for producing words in the literacy practices. Besides that, results show how much M.A. needs the use of alternative ways for communicates himself and his scholar and social inclusion; also, his writing is damaged by his physical and fine motor skill limitations. In this way, it is supposed that for M.A. writes, the first condition is the creation of alternative ways using AAC an so, writing. In other words, first he reachs the spoken language, the natural language, in the case of M.A., the alternative communication, after, the written language, the contrary it is not possible. About the AAC, it was guaranteed the individualization of M.A.'s education, respecting his pace and time in the activities...

A partir dos pressupostos teóricos da teoria histórico-cultural, do método de alfabetização Paulo Freire e dos recursos da Tecnologia Assistiva, usando como recurso didático a Prancha Fácil, esta pesquisa foi desenvolvida tendo como temática a alfabetização de alunos com deficiência. Teve como objetivo desenvolver estratégias freirianas de alfabetização para uma criança com hipótese da síndrome de Worster-Drought, utilizando como instrumento auxiliar a Comunicação Suplementar Alternativa (CSA). A pesquisa colaborativa-intervencionista, do tipo estudo de caso, cuja metodologia resultou num volumoso corpus de diálogos entre sujeito da pesquisa, sua professora e a pesquisadora, gerado durante o processo de intervenção pedagógica da prática de alfabetização de um sujeito com deficiência, no contexto de uma sala de recurso. Os dados receberam abordagem de interpretação qualitativa de cujos resultados extraíram-se inferências. Do ponto de vista da função pensamento, os resultados do teste de generalização indicam que o sujeito apresenta um desempenho cognitivo esperado para sua idade, reforçando apenas dificuldades oriundas de sua deficiência motora fina (impossibilitado de fazer representações por meio do desenho e da escrita) e de sua fala pouco inteligível. Do ponto de vista da função linguagem escrita, os resultados indicam que M.A. precisa da fala do outro para fazer valer a sua, na medida em que precisava de auxílio e mediação para produzir novas palavras nas práticas de alfabetização. Apontam, ainda, para o quanto M.A. necessita de meios alternativos para se comunicar, reforçando a urgência de fazer uso da comunicação alternativa para ampliar sua comunicação e para sua inclusão escolar e social; que a escrita de M.A. é dificultada pelas limitações físicas da oralização e da parte motora fina. Infere-se que, para M.A. escrever, a condição...
Keywords: Equipamentos de autoajuda para deficientes; Educação inclusiva; Alfabetização; Sindromes